2021
DOI: 10.1016/j.dnarep.2020.103027
|View full text |Cite
|
Sign up to set email alerts
|

Towards a comprehensive view of 8-oxo-7,8-dihydro-2’-deoxyguanosine: Highlighting the intertwined roles of DNA damage and epigenetics in genomic instability

Abstract: 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG), a major product of DNA oxidation, is a pre-mutagenic lesion which is prone to mispair, if left unrepaired, with 2′-deoxyadenosine during DNA replication. While unrepaired or incompletely repaired 8-oxodG has classically been associated with genome instability and cancer, it has recently been reported to have a role in the epigenetic regulation of gene expression. Despite the growing collection of genome-wide 8-oxodG mapping studies that have been used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 178 publications
(223 reference statements)
0
37
0
Order By: Relevance
“…H 2 O 2 treatment can directly induce DNA strand breaks as well as formation of oxidized purines (Poetsch 2020 ). Oxidized purines such as 8-oxodG can be converted to apurinic (AP) sites, which are prone to single strand break formation, which is also further enabled during the comet assay procedure (Cappelli et al 2000 ; Gorini et al 2021 ). Thus, H 2 O 2 induced lesions are subject to base excision and partly to nucleotide excision (Dizdaroglu et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 treatment can directly induce DNA strand breaks as well as formation of oxidized purines (Poetsch 2020 ). Oxidized purines such as 8-oxodG can be converted to apurinic (AP) sites, which are prone to single strand break formation, which is also further enabled during the comet assay procedure (Cappelli et al 2000 ; Gorini et al 2021 ). Thus, H 2 O 2 induced lesions are subject to base excision and partly to nucleotide excision (Dizdaroglu et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…By giving consideration to the above, various mechanisms together, we are building a better picture of how ‘damage’, or perhaps more accurately ‘modifications’, are involved in the disease process. This is leading to a better understanding of how oxidative stress, DNA damage/genomic instability, gene regulatory mechanisms and DNA repair, can influence the cellular redox status, maintain homeostasis, or contribute to, or prevent, the development or progression of various diseases (discussed in Mikhed et al [ 27 ], and Gorinin et al [ 28 ]), which include cancer [ 29 , 30 ], Alzheimer's disease [ 31 ], and other neurodegenerative diseases [ 32 ], and also ageing [ 33 , 34 ].…”
Section: Formation Repair and Consequences Of Damage To Nucleic Acidsmentioning
confidence: 99%
“…Interestingly, there is also a link between DNA damage and epigenetics. In this way, it has been found that 8-oxo-7,8-dihydro-2 -deoxyguanosine (8-oxodG) may modulate epigenetic regulation of gene expression [161].…”
Section: Epigenomicsmentioning
confidence: 99%